Gear structure of speed reducer of plate brushing machine and machining method of gear structure

By using carbon fiber reinforced composite material and helical tooth design in the brush plate reducer gear, combined with lubrication channels and cooling pipelines, the problems of poor gear vibration, noise, wear and cooling effects in the prior art are solved, and higher transmission efficiency and stability are achieved, and the service life of the equipment is extended.

CN119664875AInactive Publication Date: 2025-03-21NANDAN JILANG INDIUM IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411858443.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The gear structure of the existing brush plate reducer has problems such as high vibration and noise, serious wear and poor cooling effect, which affects the operating stability and life of the equipment.

Method used

Gears are made of carbon fiber reinforced composite materials, and helical teeth, lubrication channels and cooling pipelines are designed inside the gears. The transmission efficiency and stability of the gears are improved through progressive contact, full lubrication and efficient cooling.

Benefits of technology

It significantly reduces vibration and noise during equipment operation, extends the service life of the equipment, improves the overall operation stability, and improves the performance and consistency of the product through high-precision processing and optimization of material forming processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119664875A_ABST
    Figure CN119664875A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of mechanical parts, and discloses a plate brushing machine speed reducer gear structure and a machining method thereof.The plate brushing machine speed reducer gear structure comprises a gear lubricating channel made of a carbon fiber reinforced composite material, and the volume content of carbon fibers ranges from 60% to 70%; the helical tooth lubricating channel is arranged on the gear lubricating channel and is used for being meshed with the helical tooth lubricating channel of the other gear lubricating channel; the lubricating channel is arranged at the tooth root part of the gear lubricating channel, and the lubricating channel is uniformly distributed on the contact surface of the helical tooth lubricating channel through a plurality of outlets; and the cooling pipeline lubricating channel is arranged on the periphery of the gear lubricating channel. The carbon fiber reinforced composite material is adopted, the helical tooth design is optimized, and the lubricating and cooling system is integrated, so that the strength, the wear resistance, the cooling efficiency and the lubricating effect of the gear of the speed reducer of the plate brushing machine are effectively improved, the vibration, the noise and the wear of equipment are remarkably reduced, and the service life of the equipment is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of mechanical parts, and in particular to a gear structure of a speed reducer of a brushing machine and a processing method thereof. Background Art

[0002] In modern industrial production, brush plate machine reducers, as key transmission equipment, are widely used in various mechanical systems to reduce the speed of motor output and increase torque to achieve smooth operation of the mechanical system. Traditional brush plate machine reducers use spur gear transmission structure. Due to its relatively simple processing technology and low manufacturing cost, they have been widely used in various industrial equipment.

[0003] In the prior art, the transmission structure of the spur gear reducer is made of metal materials, which has certain strength and wear resistance. However, since the contact between the teeth of the spur gears during the meshing process is line contact, it is easy to generate large vibrations and noise when running at high speeds. At the same time, when the metal gears are running for a long time at high loads, they are prone to excessive wear due to insufficient lubrication, which affects the overall life of the equipment. In addition, in order to control the operating temperature of the equipment, a cooling device is installed on the outside of the reducer, but the cooling effect is limited and it is difficult to meet the needs of high-intensity working environments.

[0004] However, the existing gear structure of the plate brushing machine reducer has some shortcomings. First, the traditional spur gear transmission is unstable, especially under high-speed operation, which is prone to large vibration and noise, affecting the smooth operation of the equipment. Secondly, metal gears are prone to wear during long-term operation, and the design of the lubrication system is difficult to cover all gear contact surfaces, resulting in insufficient lubrication. In addition, the cooling effect of the external cooling device is limited and cannot effectively reduce the operating temperature of the gear, further aggravating the wear and deformation problems of the gear. Therefore, the prior art urgently needs an improved gear structure and processing method to improve the transmission efficiency, stability and service life of the plate brushing machine reducer. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a brush machine reducer gear structure and a processing method thereof, which solves the problems of unstable gear transmission, high noise, severe wear and poor cooling effect in the prior art.

[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions: a brush machine reducer gear structure and a processing method thereof, comprising:

[0007] The gear lubrication channel is made of carbon fiber reinforced composite material, in which the volume content of carbon fiber is 60%-70%;

[0008] A helical gear lubrication channel, disposed on the gear lubrication channel, for meshing with the helical gear lubrication channel of another gear lubrication channel;

[0009] A lubrication channel is arranged at the tooth root of the gear lubrication channel, and the lubrication channel is evenly distributed on the contact surface of the helical gear lubrication channel through a plurality of outlets;

[0010] The cooling line lubrication channel is arranged at the periphery of the gear lubrication channel, and the cooling line lubrication channel is connected to an external cooling system.

[0011] Preferably, a filter screen is provided inside the lubrication channel to prevent impurities from entering the lubrication channel.

[0012] Preferably, the heat transfer coefficient α of the gear lubrication channel satisfies the following conditions:

[0013] 0.8×10-6m2 / s≤α≤1.2×10-6m2 / s

[0014] Where α is the thermal diffusivity of the gear material.

[0015] A method for processing a gear of a brushing machine reducer comprises the following steps:

[0016] (a) Material selection: Use high modulus carbon fiber and epoxy resin, and mix them so that the volume content of carbon fiber reaches 60%-70%;

[0017] (b) Preforming: The carbon fiber cloth is stacked in an alternating manner at 0° / 90° to form a preform;

[0018] (c) Mold forming: The preform is hot-pressed in a mold at a molding temperature of 120-180° C., a molding pressure of 3-5 MPa, and a holding time of 1-2 hours;

[0019] (d) Heat treatment: The formed gear is heat treated at a temperature of 180-200°C for 3-5 hours to eliminate internal stress;

[0020] (e) Lubrication channel processing: Through laser engraving or CNC processing technology, the lubrication channel is processed inside the gear, and the channel diameter is 1-2 mm;

[0021] (f) Cooling pipeline processing: Cooling pipelines are processed on the periphery of the gear. The cooling pipeline has a diameter of 4-6 mm and adopts a spiral structure. Finally, the inner wall is coated;

[0022] (g) Gear surface processing: The gear surface is precisely processed to ensure that the tooth shape and pitch meet the design requirements, and a wear-resistant coating is applied on the gear surface.

[0023] Preferably, the lubrication channel in step (e) is processed by laser engraving, the laser wavelength used in the laser engraving process is 1064 nanometers, the engraving depth is 0.5-1 mm, the pulse laser mode is used in the engraving process, the pulse frequency is 20-50kHz, and the engraving speed is 100-200mm / s.

[0024] Preferably, the inner wall coating of the cooling pipe in step (f) is a diamond-like coating, which is applied by chemical vapor deposition. The working gas of the CVD process is methane, the working pressure is 5-10Pa, the deposition temperature is 300-400°C, and the coating thickness is 2-5 microns.

[0025] Preferably, the mold forming in step (c) adopts a vacuum-assisted molding process, and a vacuum bag is used to apply negative pressure to the preform during the molding process, and the negative pressure value is controlled at -0.05 to -0.08 MPa, the heating rate of the molding mold is 2-5°C / min, the molding temperature is 120-180°C, the molding pressure is 3-5MPa, and the holding time is 1-2 hours.

[0026] Preferably, the gear surface coating in step (g) is a ceramic-based wear-resistant coating, the coating material is aluminum oxide or zirconium oxide, the coating thickness is 10-20 microns, the coating process adopts an ion spraying method, the spraying voltage is 50-70V, the spraying distance is 100-150 mm, and after coating, a high-temperature curing treatment of 500-600°C is performed for 2-4 hours.

[0027] Preferably, the heat treatment process in step (d) includes heating in stages, with the temperature increasing by 20°C in each stage, the insulation time in each stage being 30 minutes, the final target temperature being 180-200°C, the total heat treatment time being 3-5 hours, and inert gas protection being adopted during the heat treatment process, the inert gas being nitrogen or argon, and the gas flow rate being 50-100 L / min.

[0028] Preferably, nano-alumina filler is added to the epoxy resin in step (a), the filler content is 2%-5%, the average particle size of the nano-alumina particles is 20-50 nanometers, the epoxy resin and the filler are mixed by high-speed stirring, the stirring speed is 500-1000rpm, the stirring time is 30-60 minutes, and after the mixing is completed, vacuum degassing treatment is performed, the degassing pressure is -0.08 to -0.1MPa, and the degassing time is 15-30 minutes.

[0029] Working principle: Progressive contact is achieved through helical teeth to reduce vibration and noise, improve transmission stability, and lubricant is directly delivered to the gear contact surface through the lubrication channel to ensure sufficient lubrication, reduce friction and wear, and guide the coolant flow through the cooling pipeline to quickly take away heat, prevent gears from overheating and deformation, and ensure its stability in high temperature environments.

[0030] The present invention provides a gear structure of a brushing machine reducer and a processing method thereof. It has the following beneficial effects:

[0031] 1. The present invention realizes progressive contact through helical tooth design, which significantly reduces the vibration and noise during equipment operation and improves the smoothness of transmission. At the same time, combined with the high strength and wear resistance of carbon fiber reinforced composite materials, as well as integrated lubrication channels and cooling pipeline systems, it ensures that the gears are fully lubricated and effectively cooled under high load and high temperature conditions, thereby extending the service life of the equipment and improving the overall operation stability.

[0032] 2. The present invention achieves high-precision processing of the internal lubrication channels and cooling pipes of the gears by adopting advanced processing methods such as laser engraving and chemical vapor deposition. These innovative processing techniques not only ensure the dimensional accuracy and surface finish of the channels and pipes, but also reduce the defects that would occur in traditional processing methods, significantly improve production efficiency and product consistency, and ensure the excellent performance of the gears under high-performance conditions.

[0033] 3. The present invention introduces vacuum-assisted molding technology and nano-filler mixing technology to fully eliminate internal stress and bubbles during the material molding process, thereby improving the uniformity and mechanical properties of the material. The optimization of this processing method makes the gear structure more compact and stable, thereby further enhancing the overall performance of the gear and ensuring that it can still maintain excellent working conditions under extreme working conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 A perspective view of the present invention;

[0035] Figure 2 It is a structural schematic diagram of the lubrication channel of the present invention;

[0036] Figure 3 It is a structural schematic diagram of the cooling pipeline of the present invention;

[0037] Figure 4 It is a process flow chart of the present invention.

[0038] Among them, 1. gear; 2. helical teeth; 3. lubrication channel; 4. cooling pipeline. DETAILED DESCRIPTION

[0039] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] Please refer to the attached Figure 1 - Attachment Figure 4 The present invention relates to a gear structure of a brush machine reducer and a processing method thereof. The gear is made of carbon fiber reinforced composite materials and a lubrication channel and cooling pipeline are designed inside the gear, thereby improving the strength of the gear, reducing the weight, and optimizing the cooling and lubrication performance. This embodiment will describe in detail the manufacturing method and principle of the gear structure, and explain the details of each process step to ensure that technicians in this field can reproduce the technical solution.

[0041] A gear structure of a brush machine reducer, comprising: a gear 1, made of a carbon fiber reinforced composite material, wherein the volume content of the carbon fiber is 60%-70%, and the fiber layer is arranged in a 0° / 90° staggered manner; a helical tooth 2, arranged on the gear 1, and the helical angle of the helical tooth is 15°-25°; a lubrication channel 3, with a diameter of 1-2 mm, arranged at the tooth root of the gear 1, and the lubrication channel 3 is evenly distributed on the contact surface of the helical tooth 2 through multiple outlets; a cooling pipeline 4, arranged on the periphery of the gear 1, with a diameter of 4-6 mm, and a spiral arrangement, and the cooling pipeline 4 is connected to an external cooling system.

[0042] A filter screen is provided at the entrance of the lubrication channel 3, and the aperture of the filter screen is 0.2-0.5 mm to prevent impurities from entering the lubrication channel; the thermal conductivity coefficient α of the gear 1 satisfies the following conditions:

[0043] 0.8×10-6m2 / s≤α≤1.2×10-6m2 / s

[0044] Wherein, α is the thermal diffusivity of the gear 1 material.

[0045] A method for processing the gear of a brushing machine reducer:

[0046] 1. Material selection and preforming of gear structure

[0047] First, in order to ensure that the gear has high strength, wear resistance and good thermal conductivity, the present invention selects carbon fiber reinforced composite materials as the main material of the gear. Carbon fiber has high specific strength, low density, excellent corrosion resistance and heat resistance, and is particularly suitable for application scenarios that require lightweight and high strength in high-speed rotating equipment.

[0048] In this embodiment, the material selection of the gear is as follows:

[0049] Carbon fiber type: Choose high modulus carbon fiber (such as T800 or T1000), and set the volume content of the fiber to 60%-70%. This fiber provides excellent mechanical strength and rigidity.

[0050] Resin matrix: Epoxy resin is selected as the matrix material. Epoxy resin has excellent bonding performance with carbon fiber and can maintain stability at high temperatures. In order to enhance the thermal conductivity and wear resistance of the material, 2%-5% nano-alumina filler is added to the epoxy resin, and the average particle size of the filler is 20-50 nanometers.

[0051] 2. Preparation of preform

[0052] In order to ensure that carbon fiber can effectively enhance the mechanical properties of composite materials during the molding process, the stacking method of carbon fiber cloth is very important. The stacking method of 0° / 90° staggered arrangement can effectively improve the tensile strength and shear strength of the material.

[0053] In this embodiment, the steps for making the preform are as follows:

[0054] Fiber cloth stacking: Carbon fiber cloth is stacked in an alternating manner at 0° / 90°, and the thickness of each layer of fiber cloth is controlled at 0.1-0.2 mm. A preform is formed by stacking multiple layers to achieve the required thickness and strength.

[0055] Interlayer bonding: In order to ensure a firm bond between the layers, during the fiber cloth lamination process, epoxy resin is evenly coated between each layer of fiber to ensure that the fiber and the resin are fully bonded.

[0056] Degassing treatment: After lamination is completed, the preform is placed in a vacuum environment for degassing treatment. The vacuum pressure is controlled at -0.08 to -0.1MPa and the degassing time is 15-30 minutes to ensure that there are no bubbles inside the composite material and improve the overall performance of the material.

[0057] 3. Mould forming and heat treatment

[0058] After the preform is prepared, it needs to be processed into the final shape of the gear through a mold forming process. Mold forming is an important step to ensure the dimensional accuracy and shape accuracy of the gear. This embodiment adopts a vacuum assisted forming process to ensure that the preform is evenly stressed in the mold and has high forming quality.

[0059] In this embodiment, the specific steps of mold forming are as follows:

[0060] Vacuum assisted molding: Place the preform in the mold and use a vacuum bag to apply negative pressure to the preform, with the negative pressure value controlled at -0.05 to -0.08MPa. During the mold molding process, the mold heating rate is 2-5℃ / min, the molding temperature is controlled at 120-180℃, the molding pressure is 3-5MPa, and the holding time is 1-2 hours to ensure full bonding and fluidity between the carbon fiber and the resin.

[0061] Heat treatment: After forming, the gear needs to be heat treated to eliminate internal stress and stabilize the size and shape of the material. The heat treatment process includes heating in stages, with the temperature increasing by 20°C each stage until the target temperature of 180-200°C is reached. The holding time for each stage is 30 minutes, and the total heat treatment time is 3-5 hours. During the heat treatment process, an inert gas (such as nitrogen or argon) is used for protection, with a gas flow rate of 50-100L / min to avoid oxidation and degradation of the material.

[0062] 4. Processing of lubrication channels

[0063] In order to improve the lubrication effect of the gear, a lubrication channel is designed inside the gear. The lubrication channel is processed by laser engraving or CNC processing technology to ensure the accuracy and smoothness of the channel.

[0064] In this embodiment, the processing steps of the lubrication channel are as follows:

[0065] Channel design: The diameter of the lubrication channel is designed to be 1-2 mm and is arranged at the root of the gear teeth. The channel layout adopts a spiral or linear layout to ensure that the lubricant can be evenly distributed on the contact surface of the gear.

[0066] Laser engraving: Laser engraving technology is used to process the lubrication channel. During the engraving process, a pulsed laser with a wavelength of 1064 nanometers is used, the pulse frequency is 20-50kHz, the engraving depth is controlled at 0.5-1 mm, and the engraving speed is 100-200mm / s. By adjusting the engraving parameters, the inner wall of the channel can be ensured to be smooth and burr-free, ensuring the fluidity of the lubricant.

[0067] Filter device: In order to prevent impurities from entering the lubrication channel, a filter screen with a pore size of 0.2-0.5 mm is set at the entrance of the channel. The filter screen material is stainless steel or copper alloy to ensure that it has good corrosion resistance and strength.

[0068] 5. Processing of cooling pipes

[0069] Gears generate a lot of heat when running at high speeds, so cooling pipes are designed around the periphery of the gears to improve heat dissipation efficiency. The cooling pipes are coated using the chemical vapor deposition (CVD) method to ensure cooling effects while enhancing the durability of the pipes.

[0070] In this embodiment, the processing steps of the cooling pipeline are as follows:

[0071] Pipeline design: The diameter of the cooling pipeline is designed to be 4-6 mm, and it is arranged in a spiral shape. The pipeline is arranged along the periphery of the gear to ensure that the coolant can flow evenly and fully cover the gear surface. The inlet and outlet of the pipeline are connected to the external cooling system through high-pressure sealing joints to ensure that there is no leakage in the flow path of the coolant.

[0072] Inner wall coating treatment: The inner wall of the cooling pipe is coated with diamond-like coating (DLC) with a coating thickness of 2-5 microns. The working gas of the CVD process is methane, the working pressure is 5-10Pa, and the deposition temperature is 300-400℃. The application of the coating can significantly improve the wear resistance of the pipe and reduce fluid resistance.

[0073] Spraying process: After the coating deposition is completed, plasma spraying is carried out with a spraying voltage of 50-70V and a spraying distance of 100-150mm to ensure that the coating evenly covers the inner wall of the cooling pipe.

[0074] 6. Precision machining and coating of gear surface

[0075] In order to improve the wear resistance of the gear, the gear surface is precision machined and coated with a ceramic-based wear-resistant coating. The ceramic coating is applied using plasma spraying technology to ensure that the gear surface has good wear resistance and hardness.

[0076] In this embodiment, the steps of precision machining and coating the gear surface are as follows:

[0077] Tooth profile processing: Use high-precision CNC machine tools to process the gear surface to ensure that the tooth profile and pitch meet the design requirements. The processing accuracy is controlled at ±0.01 mm, and the surface roughness Ra does not exceed 0.4 microns.

[0078] Coating material selection: The coating material is aluminum oxide (Al2O3) or zirconium oxide (ZrO2), and the coating thickness is 10-20 microns. The coating process adopts plasma spraying method, the spraying voltage is 50-70V, and the spraying distance is 100-150 mm.

[0079] High temperature curing treatment: After coating, high temperature curing treatment of 500-600℃ is carried out for 2-4 hours to ensure that the coating is closely bonded to the gear surface and to improve the hardness and wear resistance of the coating.

[0080] 7. Equipment installation and operation

[0081] After the gear is manufactured and coated, the gear can be installed in the brush plate machine reducer for use. To ensure the long-term stable operation of the equipment, the present invention provides a detailed solution for installation and operation monitoring.

[0082] In this embodiment, the steps of equipment installation and operation are as follows:

[0083] Installation steps: Install the gear to the designated position of the brush plate machine reducer, and use high-precision bearings to ensure the matching accuracy between the gear and the reducer shaft. During the installation process, attention should be paid to the connection of the lubrication channel and the cooling pipeline to ensure sealing and fluidity.

[0084] Operation monitoring: During the operation of the equipment, the temperature and lubrication status of the gears are monitored in real time through temperature sensors and pressure sensors. The control system dynamically adjusts the flow of coolant and the supply of lubricant according to the sensor data to ensure that the gears can operate stably under high-speed rotation and high-load conditions.

[0085] Maintenance: Regularly check the working status of the lubrication channel and cooling pipeline to ensure that the channel is not blocked and the pipeline is not leaking. At the same time, regularly inspect the gear surface, check the wear of the coating, and perform maintenance or replacement in time.

[0086] Embodiment 1:

[0087] Material selection:

[0088] Carbon fiber: T800, volume content 65%.

[0089] Resin matrix: epoxy resin, nano-alumina filler content 3%, particle size 30 nanometers.

[0090] Preform:

[0091] Lamination method: 0° / 90° staggered arrangement, fiber cloth thickness 0.15 mm.

[0092] Degassing treatment: vacuum pressure is -0.08MPa, time is 20 minutes.

[0093] Moulding:

[0094] Molding temperature: 160℃.

[0095] Molding pressure: 4MPa.

[0096] Holding time: 1.5 hours.

[0097] Vacuum assist: negative pressure value is -0.06MPa.

[0098] Heat Treatment:

[0099] Heating in stages: the temperature increases by 20°C in each stage and each stage is kept warm for 30 minutes.

[0100] Final target temperature: 190°C.

[0101] Total heat treatment time: 4 hours.

[0102] Inert gas protection: nitrogen, gas flow rate is 80L / min.

[0103] Lubrication channel machining:

[0104] Laser engraving: wavelength 1064 nanometers, pulse frequency 30kHz, engraving depth 0.7 mm.

[0105] Channel diameter: 1.5 mm.

[0106] Cooling pipe processing:

[0107] Inner wall coating: DLC coating, CVD process, working pressure 7Pa, deposition temperature 350℃.

[0108] Tube diameter: 5 mm, spiral arrangement.

[0109] Gear surface coating:

[0110] Coating material: Alumina (Al2O3), thickness 15 μm, plasma spraying, spraying voltage 60 V, spraying distance 120 mm.

[0111] Curing treatment: temperature 550℃, time 3 hours.

[0112] Embodiment 2:

[0113] Material selection:

[0114] Carbon fiber: T700, volume content 60%.

[0115] Resin matrix: epoxy resin, nano-alumina filler content 2%, particle size 25 nanometers.

[0116] Preform:

[0117] Lamination method: 0° / 90° staggered arrangement, fiber cloth thickness 0.2 mm.

[0118] Degassing treatment: vacuum pressure is -0.09MPa, time is 25 minutes.

[0119] Moulding:

[0120] Molding temperature: 150℃.

[0121] Molding pressure: 3.5MPa.

[0122] Holding time: 1 hour.

[0123] Vacuum assist: negative pressure value is -0.07MPa.

[0124] Heat Treatment:

[0125] Heating in stages: the temperature increases by 20°C in each stage and each stage is kept warm for 30 minutes.

[0126] Final target temperature: 185°C.

[0127] Total heat treatment time: 4 hours.

[0128] Inert gas protection: nitrogen, gas flow rate is 70L / min.

[0129] Lubrication channel machining:

[0130] CNC machined, channel diameter 1.8 mm.

[0131] Cooling pipe processing:

[0132] Inner wall coating: DLC coating, CVD process, working pressure 8Pa, deposition temperature 360℃.

[0133] Pipe diameter: 4 mm, arranged in a straight line.

[0134] Gear surface coating:

[0135] Coating material: zirconium oxide (ZrO2), thickness 20 microns, plasma spraying, spraying voltage 55V, spraying distance 130 mm.

[0136] Curing treatment: temperature 580℃, time 2 hours.

[0137] Embodiment 3:

[0138] Material selection:

[0139] Carbon fiber: T1000, volume content 70%.

[0140] Resin matrix: epoxy resin, nano-alumina filler content 5%, particle size 50 nanometers.

[0141] Preform:

[0142] Lamination method: 0° / 90° staggered arrangement, fiber cloth thickness 0.12 mm.

[0143] Degassing treatment: vacuum pressure is -0.08MPa, time is 30 minutes.

[0144] Moulding:

[0145] Molding temperature: 170℃.

[0146] Molding pressure: 5MPa.

[0147] Holding time: 2 hours.

[0148] Vacuum assist: negative pressure value is -0.08MPa.

[0149] Heat Treatment:

[0150] Heating in stages: the temperature increases by 20°C in each stage and each stage is kept warm for 30 minutes.

[0151] Final target temperature: 200°C.

[0152] Total heat treatment time: 5 hours.

[0153] Inert gas protection: argon, gas flow rate is 90L / min.

[0154] Lubrication channel machining:

[0155] Laser engraving: wavelength 1064 nm, pulse frequency 25 kHz, engraving depth 0.8 mm.

[0156] Channel diameter: 1.2 mm.

[0157] Cooling pipe processing:

[0158] Inner wall coating: DLC coating, CVD process, working pressure 9Pa, deposition temperature 370℃.

[0159] Tube diameter: 6 mm, spiral arrangement.

[0160] Gear surface coating:

[0161] Coating material: Alumina (Al2O3), thickness 12 microns, plasma spraying, spraying voltage 65V, spraying distance 110 mm.

[0162] Curing treatment: temperature 600℃, time 4 hours.

[0163] Embodiment 4:

[0164] Material selection:

[0165] Carbon fiber: T800, volume content 63%.

[0166] Resin matrix: epoxy resin, nano-alumina filler content 4%, particle size 30 nanometers.

[0167] Preform:

[0168] Lamination method: 0° / 90° staggered arrangement, fiber cloth thickness 0.15 mm.

[0169] Degassing treatment: vacuum pressure is -0.07MPa, time is 20 minutes.

[0170] Moulding:

[0171] Molding temperature: 160℃.

[0172] Molding pressure: 4MPa.

[0173] Holding time: 1.5 hours.

[0174] Vacuum assist: negative pressure value is -0.06MPa.

[0175] Heat Treatment:

[0176] Heating in stages: the temperature increases by 20°C in each stage and each stage is kept warm for 30 minutes.

[0177] Final target temperature: 195°C.

[0178] Total heat treatment time: 4 hours.

[0179] Inert gas protection: nitrogen, gas flow rate is 85L / min.

[0180] Lubrication channel machining:

[0181] CNC machined, channel diameter 1.6 mm.

[0182] Cooling pipe processing:

[0183] Inner wall coating: DLC coating, CVD process, working pressure 6Pa, deposition temperature 340℃.

[0184] Tube diameter: 5 mm, spiral arrangement.

[0185] Gear surface coating:

[0186] Coating material: zirconium oxide (ZrO2), thickness 18 microns, plasma spraying, spraying voltage 60V, spraying distance 125 mm.

[0187] Curing treatment: temperature 560℃, time 3 hours.

[0188] Embodiment 5:

[0189] Material selection:

[0190] Carbon fiber: T700, volume content 67%.

[0191] Resin matrix: epoxy resin, nano-alumina filler content 3%, particle size 35 nanometers.

[0192] Preform:

[0193] Lamination method: 0° / 90° staggered arrangement, fiber cloth thickness 0.18 mm.

[0194] Degassing treatment: vacuum pressure is -0.09MPa, time is 25 minutes.

[0195] Moulding:

[0196] Molding temperature: 155℃.

[0197] Molding pressure: 3.8MPa.

[0198] Holding time: 1 hour.

[0199] Vacuum assist: negative pressure value is -0.07MPa.

[0200] Heat Treatment:

[0201] Heating in stages: the temperature increases by 20°C in each stage and each stage is kept warm for 30 minutes.

[0202] Final target temperature: 185°C.

[0203] Total heat treatment time: 4 hours.

[0204] Inert gas protection: nitrogen, gas flow rate is 75L / min.

[0205] Lubrication channel machining:

[0206] Laser engraving: wavelength 1064 nanometers, pulse frequency 28kHz, engraving depth 0.6 mm.

[0207] Channel diameter: 1.4 mm.

[0208] Cooling pipe processing:

[0209] Inner wall coating: DLC coating, CVD process, working pressure 7Pa, deposition temperature 355℃.

[0210] Pipe diameter: 5 mm, arranged in a straight line.

[0211] Gear surface coating:

[0212] Coating material: Alumina (Al2O3), thickness 17 microns, plasma spraying, spraying voltage 58V, spraying distance 115 mm.

[0213] Curing treatment: temperature 570°C, time 2.5 hours.

[0214] Comparative Example

[0215] Comparative Example 1:

[0216] Material selection:

[0217] Carbon fiber: T700, volume content 60%.

[0218] Resin matrix: pure epoxy resin, no filler.

[0219] Moulding:

[0220] Molding temperature: 150℃.

[0221] Molding pressure: 3.5MPa.

[0222] Holding time: 1 hour.

[0223] Heat Treatment:

[0224] Single stage heating to 180°C, total heat treatment time 2 hours.

[0225] Lubrication channel processing: No lubrication channel.

[0226] Cooling pipe processing: No cooling pipe.

[0227] Gear surface coating: No coating treatment.

[0228] Comparative Example 2:

[0229] Material selection:

[0230] Carbon fiber: T800, volume content 65%.

[0231] Resin matrix: Epoxy resin, no filler.

[0232] Moulding:

[0233] Molding temperature: 160℃.

[0234] Molding pressure: 4MPa.

[0235] Holding time: 1.5 hours.

[0236] Heat Treatment:

[0237] Single stage heating to 190℃, total heat treatment time 3 hours. Lubrication channel processing: No lubrication channel.

[0238] Cooling pipe processing: No cooling pipe.

[0239] Gear surface coating: No coating treatment.

[0240] Comparative Example 3:

[0241] Material selection:

[0242] Carbon fiber: T1000, volume content 70%.

[0243] Resin matrix: epoxy resin, nano-alumina filler content 5%. Moulding:

[0244] Molding temperature: 170℃.

[0245] Molding pressure: 5MPa.

[0246] Holding time: 2 hours.

[0247] Heat Treatment:

[0248] Single stage heating to 200℃, total heat treatment time 4 hours. Lubrication channel processing: No lubrication channel.

[0249] Cooling pipe processing: No cooling pipe.

[0250] Gear surface coating: No coating treatment.

[0251] Data table:

[0252]

[0253]

[0254] Examples 1 to 5 demonstrate the diversified processing methods of the gear structure of the present invention through different carbon fiber and resin matrix formulations, molding conditions, heat treatment steps, and processing of lubrication channels and cooling lines. These examples provide excellent mechanical properties, lubricity and heat dissipation, and the process parameters can be adjusted according to specific application requirements. Comparative Examples 1 to 3 do not adopt the lubrication channel and cooling line design of the present invention, and do not perform surface coating treatment, so they are insufficient in performance.

[0255] The following experimental examples show the performance of Examples 1-5 and Comparative Examples 1-3 in a series of tests, including mechanical strength test, wear resistance test, temperature rise test, lubrication effect test and fatigue life test.

[0256] Experimental example

[0257] Mechanical strength testing: Determines the tensile and compressive strength of gear structures.

[0258] Wear resistance test: Measure the surface wear of the gear after 100 hours of continuous operation under specified load conditions.

[0259] Temperature rise test: Run for 4 hours under the specified load and measure the temperature rise of the gear.

[0260] Lubrication effectiveness test: measures the lubricant consumption of gears during continuous operation.

[0261] Fatigue life test: Determines the total time it takes a gear to fail under continuous load. Experimental data table.

[0262]

[0263]

[0264] Through the above experimental examples and data analysis, it can be clearly seen that the gear structure of the present invention and its processing method show significant advantages in mechanical strength, wear resistance, temperature rise control, lubrication effect and fatigue life. These performance advantages are derived from the high-strength carbon fiber composite materials, scientific heat treatment processes, innovative lubrication and cooling designs, and the application of wear-resistant coatings used in the present invention. These experimental data show that the gear structure of the present invention not only has advantages in theory, but also can provide better performance and longer life in practical applications, and is particularly suitable for use in high-load, high-speed brush machine reducers.

[0265] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A brush machine reducer gear structure, characterized in that: include: The gear (1) is made of a carbon fiber reinforced composite material, wherein the volume content of the carbon fiber is 60%-70%; Helical teeth (2), arranged on the gear (1) and used for meshing with the helical teeth (2) of another gear (1); A lubrication channel (3) arranged at the tooth root of the gear (1), wherein the lubrication channel (3) is evenly distributed on the contact surface of the helical teeth (2) through a plurality of outlets; A cooling pipeline (4) is arranged on the periphery of the gear (1), and the cooling pipeline (4) is connected to an external cooling system.

2. A brush machine reducer gear structure according to claim 1, characterized in that: A filter screen is arranged inside the lubrication channel (3) to prevent impurities from entering the lubrication channel.

3. The gear structure of the speed reducer of the brushing machine according to claim 1 is characterized in that: The heat transfer coefficient α of the gear (1) satisfies the following conditions: 0.8×10-6m2 / s≤α≤1.2×10-6m2 / s Here, α is the thermal diffusivity of the gear (1) material.

4. A method for processing a brushing machine reducer gear, according to a brushing machine reducer gear structure according to claims 1-3, characterized in that: The following steps are involved: (a) Material selection: Use high modulus carbon fiber and epoxy resin, and mix them so that the volume content of carbon fiber reaches 60%-70%; (b) Preforming: The carbon fiber cloth is stacked in an alternating manner at 0° / 90° to form a preform; (c) Mold forming: The preform is hot-pressed in a mold at a molding temperature of 120-180° C., a molding pressure of 3-5 MPa, and a holding time of 1-2 hours; (d) Heat treatment: The formed gear (1) is heat treated at a temperature of 180-200° C. for 3-5 hours to eliminate internal stress; (e) Lubrication channel processing: a lubrication channel (3) is processed inside the gear (1) by laser engraving or CNC processing technology, and the channel diameter is 1-2 mm; (f) Cooling pipeline processing: a cooling pipeline (4) is processed on the periphery of the gear (1), the cooling pipeline has a diameter of 4-6 mm, adopts a spiral structure, and finally the inner wall is coated; (g) Gear surface processing: The gear surface is precisely processed to ensure that the tooth shape and pitch meet the design requirements, and a wear-resistant coating is applied on the gear surface.

5. A method for processing a brush machine reducer gear according to claim 4, characterized in that: The lubrication channel (3) in step (e) is processed by laser engraving, the laser wavelength used in the laser engraving process is 1064 nanometers, the engraving depth is 0.5-1 mm, the pulse laser mode is used in the engraving process, the pulse frequency is 20-50kHz, and the engraving speed is 100-200mm / s.

6. A method for processing a brush machine reducer gear according to claim 4, characterized in that: The inner wall coating of the cooling pipeline (4) in the step (f) is a diamond-like coating, which is applied by chemical vapor deposition. The working gas of the CVD process is methane, the working pressure is 5-10Pa, the deposition temperature is 300-400°C, and the coating thickness is 2-5 microns.

7. A method for processing a brush machine reducer gear according to claim 4, characterized in that: The mold forming in step (c) adopts a vacuum-assisted molding process, and a vacuum bag is used to apply negative pressure to the preform during the molding process. The negative pressure value is controlled at -0.05 to -0.08 MPa, the heating rate of the molding mold is 2-5°C / min, the molding temperature is 120-180°C, the molding pressure is 3-5MPa, and the holding time is 1-2 hours.

8. The method for processing the gear of a brushing machine reducer according to claim 4, characterized in that: The gear surface coating in step (g) is a ceramic-based wear-resistant coating, the coating material is aluminum oxide or zirconium oxide, the coating thickness is 10-20 microns, the coating process adopts an ion spraying method, the spraying voltage is 50-70V, the spraying distance is 100-150 mm, and after coating, a high-temperature curing treatment of 500-600°C is performed, and the curing time is 2-4 hours.

9. A method for processing a brush machine reducer gear according to claim 4, characterized in that: The heat treatment process in the step (d) includes heating in stages, with the temperature increasing by 20°C in each stage, the insulation time in each stage being 30 minutes, the final target temperature being 180-200°C, the total heat treatment time being 3-5 hours, and inert gas protection being adopted during the heat treatment process, the inert gas being nitrogen or argon, and the gas flow rate being 50-100 L / min.

10. A method for processing a brush machine reducer gear according to claim 4, characterized in that: In the step (a), nano-alumina filler is added to the epoxy resin, the filler content is 2%-5%, the average particle size of the nano-alumina particles is 20-50 nanometers, the epoxy resin and the filler are mixed by high-speed stirring, the stirring speed is 500-1000rpm, the stirring time is 30-60 minutes, and after the mixing is completed, vacuum degassing treatment is performed, the degassing pressure is -0.08 to -0.1MPa, and the degassing time is 15-30 minutes.